On boundary damped inhomogeneous Timoshenko beams and related problems. (10th August 2016) - Picard, Rainer; Watson, Bruce
Abstract : We consider the model equations for the Timoshenko beam as a first‐order system in the framework of evolutionary equations. The focus is on boundary damping, which is implemented as a dynamic boundary condition. A change of material laws allows the inclusion of a large class of cases of boundary damping. By choosing a particular material law, it is shown that the first‐order approach to Sturm–Liouville problems with boundary damping is also covered. Copyright © 2016 John Wiley & Sons, Ltd.